Ready-to-run Java 3D - Brown, Kirk; Petersen, Daniel (New York : Wiley, 1999)
This text shows Web developers how to add interactive content to attract and hold Internet visitors to Websites. Readers should gain a working understanding of how Java 3D fits into other Web technologies and how to use special development tools
Getting Started; A 3D Graphics Primer; Meet the Java 3D API; Beautiful Geometry; Translation, Rotation, and Scaling; Light and Transparency; Behaviors, Interpolators, and Event Detection; Fog Effects; Texture Mapping; Java 3D Sound; 3D Text and Fonts; Java 3D Web Tools and Utilities; Appendices; Index.
Includes index.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)